Applications and Theory of Petri Nets 32nd International Conference, PETRI NETS 2011, Newcastle, UK, June 20-24, 2011. Proceedings - Kristensen, Lars M.; Petrucci, Laure (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 32nd International Conference on Applications and Theory of Petri Nets and Other Models of Concurrency, PETRI NETS 2011, held in Newcastle, UK, in June 2011. The 13 regular papers and 4 tool papers presented were carefully reviewed and selected from 49 submissions. The book also contains 3 full paper length invited talks. All current issues on research and development in the area of Petri nets and related models of concurrent systems are addressed.